2012
DOI: 10.1002/nau.21252
|View full text |Cite
|
Sign up to set email alerts
|

Overactive bladder symptoms and voiding dysfunction in neurologically normal women

Abstract: Women with impaired bladder emptying present with a wide range of LUTS, and PVR measurement is essential for diagnosis. OAB and VD can clearly coexist and accurate diagnosis of underlying pathophysiology is required. Recommendations for clinical practice and research are provided including: investigation of VD in women with OAB; evaluation of PVR values to determine appropriate therapy and identification of BOO. There is clearly a need for further research into the impact of alpha-blockers in women with VD as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…BOO in women is controversial because of the wide spectrum of symptoms associated with LUTS. Unlike anatomical BOO caused by symptomatic cystocele and uterine prolapse, previous incontinence surgery, or urethral stricture 13 , functional BOO can occur at different anatomic levels, for example, pelvic oor (dysfunctional voiding) or external urinary sphincter (Fowler's syndrome), and patients with BOO can present with storage OAB symptoms 21 . Some studies, such as that by Cho et al, reported that over 90% of women with VD exhibited OAB symptoms associated with obstruction in video-UDS ndings 8,22,23 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BOO in women is controversial because of the wide spectrum of symptoms associated with LUTS. Unlike anatomical BOO caused by symptomatic cystocele and uterine prolapse, previous incontinence surgery, or urethral stricture 13 , functional BOO can occur at different anatomic levels, for example, pelvic oor (dysfunctional voiding) or external urinary sphincter (Fowler's syndrome), and patients with BOO can present with storage OAB symptoms 21 . Some studies, such as that by Cho et al, reported that over 90% of women with VD exhibited OAB symptoms associated with obstruction in video-UDS ndings 8,22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…Uro owmetry is a potentially useful tool in clinical practice. Pressure ow study (PFS) can be used to differentially diagnose VD as being either due to BOO or detrusor underactivity (DU) based on detrusor pressure measurements 9,13 . Although PFS can provide more sophisticated measurements, it could induce possible functional urethral obstruction due to the presence of the urethral catheter 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients without urinary tract infections or other obvious pathologies (eg bladder tumour or stone), these bladder disorders include overactive bladder, voiding dysfunction and interstitial cystitis (IC). In female patients, overactive bladder and voiding dysfunction can coexist, and the underlying pathophysiology is thought to be related to detrusor instability or overactivity . Empiric medical therapy often begins with anticholinergic drugs or alpha‐blockers .…”
Section: What Is Known and Objectivesmentioning
confidence: 99%
“…Urologists should bear in mind that female OAB patients with urinary frequency have the possibility of concomitant functional BOO (measurements of post‐void residual volume might be useful), which means anticholinergics as a treatment strategy for OAB symptoms are not appropriate (probably showing poor treatment efficacy) for these patients . In fact, we sometimes experience favorable clinical outcome by administration of alpha adrenoceptor antagonists with anticholinergics for female refractory OAB patients in daily clinical practice .…”
mentioning
confidence: 99%